Holocene environmental changes in southern Kamchatka, Far Eastern Russia, inferred from a pollen and testate amoebae peat succession record - Klimaschewski A.; Barnekow L.; Bennett K.; Andreev A.; Andrén E.; Bobrov A.; Hammarlund D. (2015)
© 2015. High resolution palaeoenvironmental records in Far-Eastern Russia are rare, and the Kamchatka Peninsula is among the least studied areas of the region. This paper describes a record spanning the last ca. 11,000. yr, obtained from a bog in the southern part of Kamchatka. The radiocarbon dated core was analysed for pollen, testate amoebae, charcoal and loss-on-ignition (LOI).The vegetation during the early Holocene was dominated by grasses (Poaceae), birch (Betula) and heath (Ericaceae p. p.). Around 10,300. cal. yr BP there was a substantial change in the vegetation cover to shrub alder (Alnus viridis s.l.) stands with sedges and ferns (Polypodiophyta) as well as herbs such as meadow rue (Thalictrum) in the understory. In the surroundings of Utka peatlands started to form. The variations in the vegetation cover were most probably caused by climatic changes. At the beginning of sediment accumulation, before 10,300. cal. yr BP, the composition of the vegetation points to cooler summers and/or decreased annual precipitation. Around 10,300. cal. yr BP, changes in vegetation occurred due to rising temperatures and/or changed water regimes. Increased abundancies of dry indicating testate amoebae after 9100 cal. yr BP point to intermediate to dry soil conditions. Between 8600 and 7700 cal. yr BP tree alder (Alnus incana) was widely spread at the site which probably indicates optimal environmental conditions. The tephra layer at 381-384.5. cm (ca. 8500 cal. yr BP) produces a strong impact on the testate amoebae assemblages. At 7700 cal. yr BP there was a sudden drop of A. incana in the local vegetation. From this time on, A. incana and also A. viridis decrease continuously whereas Betula gradually increases. The upper part of the sequence (after 6300 cal. yr BP) shows higher abundancies of meadowsweet (Filipendula) and sweet gale (Myrica) pollen. After 6300 cal. yr BP, changes in testate amoebae demonstrate variable soil moisture conditions at the site. Between 3700 and 1800 cal. yr BP, wet conditions dominate as ...